Private protection against crime when property value is private information - Florian Baumann; Tim Friehe (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper analyzes private precautions against crime when the value of the property to be protected is private information. Within a framework in which potential criminals can choose between various crime opportunities, we establish that decentralized decision-making by potential victims may lead to suboptimal levels of investment in private protection. Specifically, suboptimal investment can occur when observable precautions communicate information about property value to potential offenders, even when the diversion effect of private safety measures is taken into account.
Keywords: D62; K42; 330; Sicherheitsgewerbe; Kriminalitätsökonomik; Eigentum; Asymmetrische Information; Theorie